Front Cover: Advanced Engineering Materials 10∕2017. Issue 10 (23rd October 2017) - Unknown
Abstract : The cover image, derived from a microcomputed tomography analysis and treated with a threshold based skeletonization process, shows the hierarchical pore network of an alumina foam. Thickness and color indicate different pore diameters; red: high value, blue: low value. The thickness is scaled by factor 0.2 to enable an insight 3D‐view. More details can be found in the article 1700369 by Michael Scheffler and co‐workers .